Undergraduate nursing and healthcare students’ perception of soft skills assessment in OSCE: a systematic review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Mohamad Sukeri, Siti Hajar; Che Hasan, Muhammad Kamil; Win, Kyu Kyu; Noviani, Wulan (IIUM Press, 2024)
Background: The Objective Structured Clinical Examination (OSCE) is widely recognized in healthcare education for assessing clinical skills, yet its application in evaluating soft skills is still evolving. Soft skills, such as communication, empathy, and teamwork, are essential in patientcentered care but are not consistently included in OSCE assessment. Methods: This systematic review aims to identify undergraduate nursing and healthcare students' perceptions of integrating soft skills and their assessment within OSCE. A comprehensive literature review was conducted, adhering to PRISMA guidelines, yielding 29 relevant studies published between 2017 and 2023. Studies were appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Quasi-Experimental Studies, the Critical Appraisal Skills Programme (CASP) Qualitative Research Checklist, and the Mixed Methods Appraisal Tool (MMAT). Results: Three themes emerged from the analysis: (1) Perception and satisfaction of nursing students towards OSCE, (2) Perception and satisfaction of other healthcare students towards OSCE, and (3) Implementation of soft skills in OSCE. The findings indicate a positive reception of OSCE as an objective assessment tool, with students appreciating its structure and consistency. However, students highlighted challenges related to the time constraints and stress associated with OSCEs, particularly when soft skills are evaluated. Incorporating soft skills enhances students’ readiness for real-world clinical practice, yet its assessment remains inconsistent across studies. Conclusion: Integrating soft skills into OSCE is critical for developing well-rounded healthcare professionals. Future research should focus on standardizing soft skill assessments in OSCE and exploring their impact on student performance and patient outcomes to meet the evolving demands of healthcare practice.